RTPS model assisted by flipped classroom: Is it effective in increasing self-efficacy in information literacy of students? - Lestari, Purwaning Budi; Sulisetijono, Sulisetijono; Suwono, Hadi (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2024)
The importance of self-efficacy in information literacy of Biology Education students at IKIP Budi Utomo in learning in the 4.0 era, it is necessary to apply the RTPS model assisted by the flipped classroom. The purpose of the study was to determine (1) a description of the information literacy self-efficacy profile, and (2) the effectiveness of the RTPS model assisted by flipped classroom on the information literacy self-efficacy of biology education students. Type of quasi-experimental research. The number of samples N = 56 students, with the experimental class using the RTPS model assisted by a flipped classroom, number of participants N = 29, and the control class using the RT model, number of participants N = 27. Student worksheets and questionnaires served as the study's instruments. Data analysis techniques used descriptive analysis and Anacova statistical analysis to answer the hypothesis. The Anacova test used the SPSS 26 program. The results of the study showed the highest average profile value on the communication and information dissemination indicator with an average of 85 in the experimental class, conversely, the average value of 55 is the lowest profile on the information search indicator. The pre-requisite test obtained normal and homogeneous results. Continued with the results of the Anacova test, there was a significant difference in the RTPS model assisted by flipped classroom on the self-efficacy of information literacy of Biology Education students with sig.<0.05. The results of the difference in the corrected average increase were 41 in the experimental class and 20 in the control class. The conclusion is that the RTPS model assisted by a flipped classroom is effective in increasing self-efficacy in information literacy. The RTPS model assisted by flipped classrooms can be applied to more students in several universities so that students' self-efficacy in information literacy increases.